Tourism destination brand dimensions: an exploratory approach - José Manuel Cristóvão Veríssimo; Maria Teresa Borges Tiago; Flávio Gomes Tiago; João Sérgio Jardim (Tourism & Management Studies)
Recently, researchers have suggested using destination branding as a powerful marketing tool. Despite its apparent value, there appears to be little applied research on this subject that goes beyond the conventional destination brand image, especially regarding research that combines different brand equity dimensions. This study is designed to address this gap, using the islands of Madeira as a unit of research. For this purpose, a survey was undertaken of 321 tourists, in seven hotels at this destination. Respondents were requested to rate the factors for awareness, image, perceived quality, and loyalty, in a method consistent with the brand equity model, using descriptive analyses and a confirmatory factor analysis. The results show that these four dimensions are relevant for the composition of destination brand equity. Even though image shows the greatest imp